Interdiscursivity in McCormick’s Sold: A Critical Discourse Analysis - Joshi, Dipak Raj (Contemporary Research: An Interdisciplinary Academic Journal, 2019)
This paper aims to analyze the manifestation of interdiscursivity in Patricia McCormick’s novel Sold in the light of supportive, essentialist, traditional, patriarchal discourse conventions versus contradictory, hybrid, mixed discourses of change. The paper approaches the subject from the perspective of critical discourse analysis, feminist discourse analysis, and James Paul Gee’s semiotic system of seven building tasks of language. McCormick’s representation of girl trafficking in Nepali rural areas and her exoticizing of the society is found to be guided by her prior assumption and generalization of the third world countries. In spite of the presence of counter-discourses like government action, social protest organizations, joint effort against trafficking, the author only highlights Western discourse conventions vis-à-vis the third world like submissive womanhood, patriarchy, poverty, subsistent economy, and illiteracy. The paper discovers that the novelist, like a researcher, uses vignettes as tools for investigating into Nepali society, but they show her subscription to Western interdiscursivity, which makes her blind to the reformative measures afoot in Nepal to arrest the situation of girl trafficking. The novel is about a social problem but the novelist’s efforts are seen to be invested in effeminizing, romanticizing or exoticizing the Nepali society rather than in improving the situation.